Summer nights with the Maverick - Rimmer, Christine (Rimmer, Christine. Montana Mavericks. Brothers & Broncos, 2022)
He's a hero in spurs But just for tonight Ever since rancher Weston Abernathy rescued waitress Everlee Roberts at Doug's bar, he can't get her off his mind. But the spirited single mom has no interest in a casual relationship, and Wes isn't seeking commitment. As the temperature rises, Evy feels the heat, too, tempting her to throw her hat in the ring regardless of what it might cost her heart...